Integrative Science Learning in Improving Understanding of Nutrient and Nutrition Materials/Pembelajaran Sains Integratif Dalam Meningkatkan Pemahaman Materi Nutrisi dan Gizi - Agus Mukti Wibowo; Rizki Amelia (STAI Ma'had Aly Al-Hikam Malang, 2021)
Concepts in science material have characteristics related to concepts in one subject matter, between materials and with concepts outside other concepts or with other disciplines. To be able to understand this concept, an integrative understanding of the concept is needed. One of the materials that require an integrative understanding is material about nutrition and nutrition. This study used a descriptive design to describe an integrative understanding of nutrients and nutrition materials. The method used was a test and interview guide. The results showed that (1) most of the respondents were not able to provide an explanation of the benefits of chewing food both in terms of the digestive system, the type of food digested and integrative explanations with the relationship between concepts, (2) respondents experienced failure to explain the presence of enzymes in the digestive system. mechanics, (3) most of the research respondents did not yet have the ability about the relationship between the function of fiber in food and nutrition for the digestive system, (4) the respondents were unable to explain the function of fiber, nutritional content in food, nutritional function and how to manage and utilize nutrients. Failure to understand this concept may also be due to failure to understand previous concepts related to, for example, the circulatory system of animals.